Exploring multimodality, literacy and learning with young adult fiction - Melissa Schieble (Revista Interuniversitaria de Formación del Profesorado)
The author examines how preservice English teachers engaged a sociocultural and critical approach to literacy instruction and the tools of a web-based classroom to discuss young adult fiction with adolescents. A sociocultural approach to literacy instruction emphasizes meaning making as an iterative process between text and a reader's lived social, cultural and linguistic experiences. The author planned and facilitated this project with a secondary language arts teacher as part of a semester long course on adolescent literature from 2006-08.